Nucleation under the impact of pulsed laser radiation - Maksimovsky, Sergey Nikoloaevich; Stavtsev, Aleksey Urievich (Nexo Revista Científica, 2021)
The article shows theoretical calculations of nucleation in nonequilibrium conditions under the impact of high-power laser radiation, and their experimental confirmation. The phase transition during homogeneous nucleation without seed in the gas phase has long been studied by various scientists in the developed countries of the world. Several nucleation theories have been developed, however, they are difficult or impossible to apply to fast-flowing crystallization processes occurring at high pressures and temperatures that take place when using high-power laser radiation in the gas phase. In this article, an extended model of nucleation in the gas phase is developed using traditional thermodynamic concepts, as well as the influence of the process conditions on the equilibrium concentration and the formed particle size within the range from 100 nm to 1 micron is predicted. The article describes experiments on growing structures on plastic substrates containing inside optical inhomogeneities in the form of diffraction gratings. The calculation of the sublimation evaporation pressures of aluminum is conducted depending on different laser radiation power densities. The authors obtained images of nascent structures by electron microscopy and demonstrated the possibility of observing the nucleation phases in situ by changing the power of laser radiation of the sample.